Using multiliteracies and multimodalities to support young children's learning - Charles, Marie; Boyle, Bill (William F.) (SAGE, 2014)
"Grounded in classroom practice, this practical book shows trainees and current teachers how to scaffold children's literacy using a creative and supportive approach. It offers teaching strategies for Multiliteracies (fiction, expository/instructions, poetry, recount) and Multimodalities (reading, writing, speaking, listening, performing, illustrating) and helps to develop a relationship between teacher and learner."--Page 4 of cover.